2018
DOI: 10.1016/j.psep.2018.03.024
|View full text |Cite
|
Sign up to set email alerts
|

Effect of advanced catalysts on tire waste pyrolysis oil

Abstract:  Catalytic and non-catalytic pyrolysis of tire waste was carried out at pilot-scale  Non-catalytic pyrolysis produced highest liquid oil as compared to catalytic pyrolysis  Natural zeolite, zeolite (H-SDUSY), Al2O3 and Ca(OH)2 catalysts were used  Use of various catalysts improved the quality of liquid oil  Oil from both processes mainly contained aromatic with some aliphatic compounds

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(39 citation statements)
references
References 62 publications
1
27
0
2
Order By: Relevance
“…While preparing the pyrolysis oil, it is suggested that the catalysts should be used in order to increase the liquid proportion in the yield. In this regard Miandad, et al [30] performed gas chromatography-mass spectrometry analysis and found that use of catalyst like activated alumina for the production of waste tyre pyrolysis oil reduced the aromatic hydrocarbon compounds to 60.9% compared to 93.3% when produced without catalyst. Salan et al [31] have also used catalysts like clinoptilolite and meerschaum for the catalytic pyrolysis of pulper rejects and compared their performance.…”
Section: Tyre Pyrolysis Oil-methods and Applicationsmentioning
confidence: 99%
“…While preparing the pyrolysis oil, it is suggested that the catalysts should be used in order to increase the liquid proportion in the yield. In this regard Miandad, et al [30] performed gas chromatography-mass spectrometry analysis and found that use of catalyst like activated alumina for the production of waste tyre pyrolysis oil reduced the aromatic hydrocarbon compounds to 60.9% compared to 93.3% when produced without catalyst. Salan et al [31] have also used catalysts like clinoptilolite and meerschaum for the catalytic pyrolysis of pulper rejects and compared their performance.…”
Section: Tyre Pyrolysis Oil-methods and Applicationsmentioning
confidence: 99%
“…The use of calcium carbonate (CaCO 3 ) in the pyrolysis of horse manure allows for lower temperatures due to the catalytic effects of CaCO 3 as a possible source of CO 2 [34]. Co-pyrolysis of different plastic mixtures [35], as well as the use of catalysts [36][37][38][39], has also yield interesting results concerning the productivity and quality of the PDO components.…”
Section: Pyrolysismentioning
confidence: 99%
“…O catalisador básico foi utilizado também com objetivo sequestrar o enxofre presente na borracha vulcanizada dos pneus. 16 Os resultados estão resumidos na Tabela 5.…”
Section: Pirólise Catalítica -Unidade De Bancadaunclassified
“…Os resultados indicam que a adição de 10 % de CaO aparentemente piora as condições de troca térmica no reator, levando a uma pirólise incompleta da borracha inicial. Miandad e colaboradores 16 obtiveram resultado semelhante utilizando Ca(OH)2, com 55 % de resíduo sólido. Com relação à capacidade de sequestro de enxofre durante a pirólise, a presença de CaO levou a uma redução modesta, mas significativa, da quantidade de enxofre na fração líquida de 0,77 para 0,58 %, uma redução de 24 %.…”
Section: Pirólise Catalítica -Unidade De Bancadaunclassified